2016
DOI: 10.1155/2016/6021798
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Kinetic Study of the Sorption of Carbon Dioxide onto Amine-Treated Oil Fly Ash

Abstract: A new CO2adsorbent is produced from waste oil fly ash (OFA). Ammonium hydroxide solution is used to convert OFA to activated carbon. Then, the product is used for the adsorption of CO2from a nitrogen/carbon dioxide (N2/CO2) gas mixture. The OFA samples are characterized by several techniques. Chemical treatment of OFA considerably changed its surface morphology. In particular, its surface area, as determined by BET measurements, increased from 59 to 318 m2/g. The amine-functionalized ash had a monolayer adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Δ G ads , Δ H ads , and Δ S ads values for pure and treated with surfactant carbonate are computed in Table . Negative Δ H ads values confirm the exothermic nature of CH 4 and CO 2 adsorption on pure carbonate. , At 50 °C the values of Δ G ads for CO 2 and CH 4 on pure carbonate are less than that of treated limestone underlining high adsorption spontaneity . As the temperature was raised to 100 and 150 °C, the values of Δ G ads for CO 2 and CH 4 on treated carbonate decreases revealed the favored spontaneity at 100 and 150 °C because thermal energy is higher than adsorption energy.…”
Section: Results and Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Δ G ads , Δ H ads , and Δ S ads values for pure and treated with surfactant carbonate are computed in Table . Negative Δ H ads values confirm the exothermic nature of CH 4 and CO 2 adsorption on pure carbonate. , At 50 °C the values of Δ G ads for CO 2 and CH 4 on pure carbonate are less than that of treated limestone underlining high adsorption spontaneity . As the temperature was raised to 100 and 150 °C, the values of Δ G ads for CO 2 and CH 4 on treated carbonate decreases revealed the favored spontaneity at 100 and 150 °C because thermal energy is higher than adsorption energy.…”
Section: Results and Discussionmentioning
confidence: 75%
“…49,50 At 50 °C the values of ΔG ads for CO 2 and CH 4 on pure carbonate are less than that of treated limestone underlining high adsorption spontaneity. 51 As the temperature was raised to 100 and 150 °C, the values of ΔG ads for CO 2 and CH 4 on treated carbonate decreases revealed the favored spontaneity at 100 and 150 °C because thermal energy is higher than adsorption energy. Correspondingly, these findings suggest that at a temperature range of 100−150 °C (which is the range for most of the gas reservoirs), the adsorption of CO 2 is much more preferred to that of CH 4 , which can be attributed to the high selectivity and affinity of calcite minerals toward capturing CO 2 .…”
Section: Methodsmentioning
confidence: 95%
“…The selective adsorption of CO 2 from a CO 2 /N 2 mixture utilizing previously discussed AC was investigated by Yaumi et al [44] while the sorption kinetic study was conducted by Saad et al [102] It was reported that the maximum adsorption capacity of 240 mg g À 1 was achieved using chemically treated HFOA. It was also stated that the adsorption was dependent on the CO 2 concentration, gas flow rate, and temperature and humidity, as it increased with an increase in these parameters.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…The sorption studies evaluated 1.3 mmol g −1 of CO 2 at 25°C [31]. In a similar study, the activated carbon produced from waste oil fly ash was used as CO 2 adsorbent by Saad et al [32]. The carbon material was used to capture CO 2 (74.5 mg g −1 ) from a mixture of N 2 and CO 2 and the chemisorbed amount of the gas increased over a temperature range, 0-40°C.…”
Section: Introductionmentioning
confidence: 99%